Immunological biomarkers in neuropsychiatric systemic lupus erythematosus: a comparative cross-sectional study from a tertiary care center in South India. (April 2020) - Seth, G; Sundaresh, A; Mariaselvam, C M; Kumar, G; Chengappa, K G; Adarsh, M B; Tamouza, R; Negi, VS
Introduction: The prevalence of various immunological biomarkers in neuropsychiatric systemic lupus erythematosus (NPSLE) differs among various patients with varied neuropsychiatric manifestations and different populations. We studied the prevalence of these biomarkers; especially the neuron specific autoantibodies in patients with systemic lupus erythematosus (SLE) and compared them among patients with and without neuropsychiatric involvement. Methodology: This is a comparative cross-sectional study conducted in a tertiary care hospital in South India. The prevalence of immunological biomarkers including complement levels, systemic and brain specific autoantibodies (anti-myelin antibody, anti–myelin oligodendrocyte glycoprotein and anti–myelin-associated glycoprotein antibody) were assessed and compared among those with and without NPSLE and with different NPSLE manifestations. Results: A total of 522 SLE patients were enrolled in the study. The mean age of the study participants was 28.5 ± 8.8 years and 93.5% were women. Neuropsychiatric manifestations were seen in 167 (32%) patients. Seizure was the most common neuropsychiatric manifestation seen in 41.3%, followed by psychosis (18.6%), mood disorder (16.8%), stroke (10.8%), mononeuropathy (10.2%), headache (9.6%), acute confusional state (6.6%) and aseptic meningitis (5.4%). Patients with NPSLE had a higher SLE disease activity index score. Most of the autoantibodies, that is anticardiolipin antibody (aCL), anti–β2 glycoprotein 1 antibody (β2GP1), lupus anticoagulant (LA), anti-nucleosome, anti–ribosomal P, anti-Ro52, anti-Ro60 and anti-La, were seen in higher proportion in the NPSLE group, although the difference failed to reach statistical significance. On subgroup analysis, psychosis was significantly higher in patients with anti-ribosomal P positivity than without (11.8% versus 4.1%, p.0.007; odds ratio (OR) 3.1, confidence interval (CI) 1.4–6.8), while stroke had a higher proportion among those with positive b2GP1 IgG (6.3% versus 1.8%, p.0.03; OR 3.6, CI 1.2–11.0). A higher proportion of demyelination was seen among the LA positive than the negative (10.3% versus 0.2%, p.0.03; OR 5.39, CI 1.15–24.17) and anti–myelin oligodendrocyte glycoprotein in mood disorder (14.3% versus 3.4%, p  = 0.03; OR 4.66, CI 1.13–19.13). Conclusion: No single biomarker correlated with NPSLE. Among different NPSLE manifestations, the prevalence of IgG β2GP1 in stroke, LA in demyelination, anti–ribosomal P in psychosis and anti–myelin oligodendrocyte glycoprotein in mood disorder were higher. Further studies on the pathogenic mechanisms underlying NPSLE and its different manifestations may help us to identify better biomarkers.